Загальна характеристика законодавства України про іпотеку - Чанишева, Аліна Рашидівна; Чанишева, Алина Рашидовна; Chanisheva, А. (My University, 2013)
The article is devoted to general characteristic of mortgage legislation of Ukraine. The main laws that belong to different branches of law and form the mortgage legislation are being examined, complex conclusions are made on improvement thereof and different approaches to overcoming existing collisions of the researched normative acts.
Чанишева А. Р. Загальна характеристика законодавства України про іпотеку / А. Р. Чанишева // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 324-331.
Keywords: характеристика чинних нормативно-правових актів про іпотеку в Україні; усунення суперечностей та прогалин у законодавстві України про іпотеку; законодавство України про іпотеку; характеристика действующих нормативно-правовых актов об ипотеке в Украине; устранение противоречий и пробелов в законодательстве Украины об ипотеке; законодательство Украины об ипотеке.; characterization of the existing legal acts of the mortgage in Ukraine; elimination of contradictions and gaps in the legislation of Ukraine on the mortgage; Ukrainian law on the mortgage